Novel Desorber for Online Drilling Mud Gas Logging - Marcin Lackowski; Marek Tobiszewski; Jacek Namieśnik (Journal of Analytical Methods in Chemistry)
This work presents the construction solution and experimental results of a novel desorber for online drilling mud gas logging. The traditional desorbers use mechanical mixing of the liquid to stimulate transfer of hydrocarbons to the gaseous phase that is further analyzed. The presented approach is based on transfer of hydrocarbons from the liquid to the gas bubbles flowing through it and further gas analysis. The desorber was checked for gas logging from four different drilling muds collected from Polish boreholes. The results of optimization studies are also presented in this study. The comparison of the novel desorber with a commercial one reveals strong advantages of the novel one. It is characterized by much better hydrocarbons recovery efficiency and allows reaching lower limits of detection of the whole analytical system. The presented desorber seems to be very attractive alternative over widely used mechanical desorbers.